2021
DOI: 10.3390/ijerph182312511
|View full text |Cite
|
Sign up to set email alerts
|

Oral Manifestations of COVID-19 in Hospitalized Patients: A Systematic Review

Abstract: Background: COVID-19 disease first appeared in 2019 and quickly spread worldwide, causing a global pandemic. The oral cavity represents a target of SARS-CoV-2, and oral lesions are observed in both non-hospitalized and hospitalized patients. This systematic review aims to investigate the frequency of oral manifestations in COVID-19 hospitalized patients. Methods: An electronic search was conducted in PubMed, Scopus, and Web of Science databases, including articles published up to September 2021. The review pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 97 publications
(293 reference statements)
1
47
0
4
Order By: Relevance
“…After title/abstract screening, three records, one evaluating the risk of virus contamination during minimally invasive surgery [ 19 ], one limiting the investigation to oral manifestations in children [ 20 ] and one reporting lesions observed following COVID-19 vaccination [ 21 ], were excluded. Finally, 12 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] compliant with the eligibility criteria were included in the present systematic review of systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After title/abstract screening, three records, one evaluating the risk of virus contamination during minimally invasive surgery [ 19 ], one limiting the investigation to oral manifestations in children [ 20 ] and one reporting lesions observed following COVID-19 vaccination [ 21 ], were excluded. Finally, 12 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] compliant with the eligibility criteria were included in the present systematic review of systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the twelve systematic reviews included in the present study, detailed in Table 1 , all resulted to have been published in the English language between 11 September 2020 and 27 April 2022; the full texts were all available, and two authors [ 30 , 32 ] declared funding. Two systematic reviews exclusively comprised case reports and case series [ 27 , 32 ], with one also including letters to the Editor and comments [ 33 ], whilst the remaining nine [ 22 , 23 , 24 , 25 , 26 , 28 , 29 , 30 , 31 ] also considered observational cross-sectional and/or retrospective and/or prospective studies. Three systematic reviews included a meta-analysis [ 23 , 28 , 30 ], and all resulted to be of a critically low quality, except for Doceda et al’s [ 26 ], Nijakowski et al’s [ 28 ] and Orilisi et al’s [ 29 ] studies, characterized by low quality, as per the AMSTAR2 tool assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we tended to exclude COVID-19 vaccine-related oral manifestations, as the vaccine program in Italy for kids only started in November 2021, and further studies have shown that such manifestations occur extremely rarely [ 34 ]. A study comparing COVID-19-related oral manifestations in hospitalized vs. non-hospitalized subjects has shown that such manifestations are often to be ascribed to medical devices and treatments, prone position, and immunological impairment, rather than to COVID-19 itself [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the articles’ full text, 19 additional papers were excluded (see Figure 1 ) for a total of 69 papers in the final review. Methodology reported based on Orilisi et al [ 50 ].…”
Section: Methodsmentioning
confidence: 99%